TELE ENT: A Step Forward in Providing Specialist Services in Far Remote Areas - Asif Zafar Malik ,Nousheen Qureshi , Tabassum Azim, Faisal Murad (Journal of Rawalpindi Medical College, 2017)
To study the utility of tele medicine in providing ENT services to far remote areas Methods: In this descriptive study 2 hourly weekly consultations were given by ENT consultants on every friday in Tele Medicine office. Four remote areas were connected through strong satellite Connectivity of 512 Kbs and 1 MB to Pindi through video conferencing with real time imaging modality was used. The tools used to diagnose the patients were video Otoscope to examine the ear, video endoscope and tongue depressor for oral cavity examination. Routine blood and urine examination along with required other specific tests like x-Ray, pure tune audiometry were advised accordingly, then patients were given treatment for their specific problem and given dates for follow up visit. Some patients were booked for surgery and given date of admission in our hospital. Only some patients with laryngeal and nasal problems were asked to visit the OPD for a clearer and better diagnosis as nasal and laryngeal examination could not be done through video conferencing. Patients who were given time for surgery got their investigations done in their home town and were admitted straightaway as they arrived in our hospital. These patients were scheduled for surgery on the next list, and were successfully operated and followed up post operatively. Results: A total of 2159 patients were included in our study, two third of which were females and rest male. Majority of our patients had ear problem followed by throat and nasal problems 1287 of our patients were successfully managed conservatively through video conferencing. A total of 792 patients were referred to us in Holy Family Hospital out of which 661 were successfully operated and out of these patients 459 were followed up postoperatively through video conferencing. The major operations done were Tonsillectomy, Septoplasty, Endoscopies (direct laryngoscopies and esophagoscopies), mastoidectomies, and thyroidectomy. A few emergency cases like foreign body nose and ear removal along with foreign body throat removal, incision of peritonsillar abscess and mastoid abscess were also done. Conclusion: Video conferencing in ENT is an effective tool and method of assessing and treating ENT conditions. Through Tele ENT potential surgical admissions can be screened